Reliability Evaluation of Structures Excited by Earthquakes in Time Domain Using a Novel Concept - J. Ramon Gaxiola-Camacho; Achintya Haldar; Aaron Gutierrez-Lopez (Science and Technology: Developments and Applications Vol. 3, 2025)
A novel reliability evaluation method for structures excited by the seismic loading applied in the time domain is presented. Major sources of nonlinearity and uncertainty are incorporated into the algorithm. Structures are represented by finite elements. To demonstrate that the algorithm will work in different computational platforms, the stress-based finite element is used. Connections are more realistically considered partially restrained (PR) with different rigidities. Multiple site-specific design earthquake acceleration time histories are numerically generated using information on the seismic activities of the region using the broadband platform (BBP) available at the Southern California Earthquake Center (SCEC). The reliability of structures is estimated by exciting them with real and artificially generated earthquake time histories. The accuracy of the method is verified using Monte Carlo Simulation. With the help of examples, it is demonstrated that the proposed reliability concept is efficient and accurate. The procedure can extract the reliability information with the help of a few hundred deterministic analyses instead of millions needed for simulation and users can use any computer available to them. Post-Northridge PR beam-to-column connections are superior to the pre-Northridge FR connections. Structural reliabilities are estimated for the overall lateral deflection and inter-story drift limit states. Inter-story drifts are more critical than the overall lateral deflections. The Performance-Based Seismic Design (PBSD) guidelines are briefly discussed. The reliability method fills a knowledge gap and helps to implement the PBSD concept. Currently, the authors call the method REDSET (Reliability Evaluation of Dynamic Systems Excited in Time Domain). REDSET appears to be an exciting development replacing the classical random vibration concept and providing an alternative to the simulation approach.